Assessment of landscape changes under different urban dynamics based on a multiple-scenario modeling approach. (October 2020) - Xu, Chao; Haase, Dagmar; Su, Meirong; Wang, Yutao; Pauleit, Stephan
In the context of rapid urbanization, it remains unclear how urban landscape patterns shift under different urban dynamics, in particular taking different influencing factors of urban dynamics into consideration. In the present study, three key influencing factors were considered, namely, housing demand, spatial structure, and growth form. On this basis, multiple urban dynamic scenarios were constructed and then calculated using either an autologistic regression–Markov chain–based cellular automata model or an integer programming-based urban green space optimization model. A battery of landscape metrics was employed to characterize and quantitatively assess the landscape pattern changes, among which the redundancy was pre-tested and reduced using principal component analysis. The case study of the Munich region, a fast-growing urban region in southern Germany, demonstrated that the changes of the patch complexity index and the landscape aggregation index were largely similar at sub- and regional scales. Specifically, low housing demand, monocentric and compact growth scenarios showed higher levels of patch complexity but lower levels of landscape aggregation, compared to high housing demand, polycentric and sprawl growth scenarios, respectively. In contrast, the changes in the landscape diversity index under different scenarios showed contrasting trends between different sub-regional zones. The findings of this study provide planners and policymakers with a more in-depth understanding of urban landscape pattern changes under different urban planning strategies and its implications for landscape functions and services.